Bioprosthetic valve fracture during valve-in-valve transcatheter aortic valve replacement: multicenter propensity matched analysis. (3rd October 2022) - Bonnet, G; Panagides, V; Vincent, F; Faroux, L; Corona, S; Modine, T; Metz, D; Van Belle, E; Pibarot, P; Leroux, L; Rodes-Cabau, J; Ternacle, J
Abstract: Background: Valve-in-valve (ViV) transcatheter aortic valve implantation (TAVI) can be completed by bioprosthetic valve fracture (BVF) to reduce final transvalvular gradients. The aim was to compare outcomes in ViV-TAVI patients with versus without BVF. Methods: Consecutive patients undergoing ViV-TAVI procedure in four international centers were included, from 2010 to 2021. We used a 1:2 propensity score-matching method to compare postprocedural hemodynamic, complications, and long-term outcomes. Patients were matched for baseline characteristics, time since prior surgery, and characteristics of surgical bioprothesis (type and size). Results: A total of 390 patients were analyzed, including 40 BVF. Propensity matching 1:2 yielded 38 patients in BVF group and 76 patients in no-BVF group. There was no difference in procedural complications rate and in-hospital deaths (5.1%) between the two groups. Post-procedural hemodynamic parameters significantly improved using BVF: aortic valve area (1.4 cm 2 [IQR: 1.23 to 2.3] vs. 1.3 cm 2 [IQR: 1.05 to 1.61], p=0.008), mean aortic gradient (12mmHg [IQR: 7.5 to 16.5] vs. 17mmHg [IQR: 11 to 22], p=0.008) and peak velocity (2.2m/s [IQR: 1.8 to 2.7] vs. 2.6m/s [IQR: 2.2 to 3.1], p=0.027). BVF had an additional benefit in the smallest surgical valve (≤21 mm). The use of BVF was independently associated with improved hemodynamic parameters. Overall survival in the matched cohort was 87.8±3.7% at 2-year follow-up, without difference between groups (87.5±6.9% in the BVF group vs. 88.4±4.2% in the no-BVF group, p=0.85). Conclusion: Compared to ViV-TAVI alone, BVF was safe and improved immediate hemodynamic and long-term outcomes, especially in patients with small surgical aortic bioprosthesis. Funding Acknowledgement: Type of funding sources: None.